Onto the differences in formulating micro-/nanoparticulate drug delivery system from Thai silk and Vietnamese silk: A critical comparison - Ngoc Yen Nguyen; Thi Ngoc Phuong Nguyen; Nguyen Ngoc Huyen; Van De Tran; Tran Thi Bich Quyen; Huynh Vu Thanh Luong; Duy Toan Pham (Heliyon, 2023)
Silk fibroin is a natural polymer with physicochemical properties heavily dependent on its silkworm sources and cultivation conditions. Hence, this study critically compared the characteristics and capacity to generate micro-/nanoparticles of fibroin extracted from the Thai silk and Vietnamese silk. Both Thai fibroin (SFT) and Vietnamese fibroin (SFV) were extracted and fabricated into micro-/nanoparticles using the same methods of desalination and condensation, respectively. Firstly, the amino acid compositions of SFT and SFV were determined and found to be similar, suggesting that the different cultivation conditions did not alter the fibroin chemical contents. Secondly, utilizing various analytical techniques, the SFT structure revealed less heavy chains, more light chains and P-25 glycoproteins, and lower crystallinity than those of SFV. Accordingly, compared to the particles formed by SFT, the SFV-based particles were significantly bigger (∼1700 nm vs. ∼150 nm), and possessed less drug (Amphotericin B) entrapment efficiency (64.3 ± 4.4% vs. 79.3 ± 5.1%), higher hemototoxicity, and less biostability in the blood. Conclusively, these differences add more insights for the appropriate applications of each fibroin kind to best promote its qualities and effectiveness.